Costs and Financing of Higher Education in Francophone Africa - Brossard, Mathieu; Foko, Borel (Washington, DC : World Bank, 2012)
This study is a follow-up to the Higher Education for Francophone Africa's Development Conference, held from June 13 to 15, 2006 in Ouagadougou at the initiative of the World Bank in collaboration with the Government of Burkina Faso, the French Ministry of Foreign Affairs, and the Agence Universitaire de la Francophonie. It continues and expands upon discussions that took place during that event. This study includes two sections. The first analyzes the expenditure for the higher education in the countries of French-speaking Africa by adopting a dual comparison approach: (i) chronologically, for the last 15 years, and (ii) inter alia, in particular juxtaposing French-speaking Africa compared to other developing regions. The second part presents financial simulation models in regard to national higher education development plans for the countries of French-speaking Africa.